PENGARUH KOSA KATA BAHASA INGGRIS, DASAR KOMPUTER DAN AKUNTANSI TERHADAP PRESTASI BELAJAR MYOB - Pradhana, Darojatun Yakti; Latifah, Lyna (Fakultas Ekonomi, Universitas Negeri Semarang, 2013)
The purpose of this study was to determine the influence either partially orsimultaneously of English vocabulary mastery, basic computer and basic accountingtoward the learning achievement of MYOB accounting computer at class XI AccountingSkills Competency at SMK N 1 Bawang in the academic year of 2011/2012. Thepopulation of the study was 94 students and they were all the respondents. The datawere collected by test and documentation. Then, the data were analyzed by percentagedescriptive analysis and multiple linear regression analysis. The result of the studyshowed that simultaneously, English vocabulary mastery, basic computer and basicaccounting influenced the learning achievement significantly for 23.7%, partiallyEnglish vocabulary mastery influenced the MYOB accounting computer learningachievement for 7.95%, basic computer mastery influenced it for 5.15%, and basicaccounting mastery influenced it for 7.51%. It means that the good mastery of Englishvocabulary, basic computer and basic accounting can improve the learningachievement of MYOB accounting computer.